NLRP3-activated bone marrow dendritic cells play antileukemic roles via IL-1β/Th1/IFN-γ in acute myeloid leukemia. (1st November 2021) - Liu, Qinqin; Hua, Mingqiang; Zhang, Chen; Wang, Ruiqing; Liu, Jinting; Yang, Xinyu; Han, Fengjiao; Hou, Ming; Ma, Daoxin
Abstract: The bone marrow microenvironment of acute myeloid leukemia (AML) characterized by immunosuppressive features fosters leukemia immune escape. Elucidating the immunosuppressive mechanism and developing effective immunotherapeutic strategies are necessary. Here, we found that the Th1% and IFN-γ level were downregulated in bone marrow of AML and NLRP3-activated BMDCs promoted CD4 + T cell differentiation into Th1 cells via IL-1β secretion. However, IFN-γ-producing Th1 cells were not induced by NLRP3-activated BMDCs in the presence of the NLRP3 inflammasome inhibitor MCC950 or anti-IL-1β antibody in vitro unless exogenous IL-1β was replenished. This inhibitory effect on Th1 differentiation was also observed in Nlrp3 −/− mice or anti-IL-1β antibody-treated mice. Notably, elevated Th1 cell levels promoted apoptosis and inhibited proliferation in leukemia cells via IFN-γ secretion in vitro and in vivo . Thus, NLRP3-activated BMDCs promote the proliferation of IFN-γ-producing Th1 cells with antileukemic effects and may provide insight into the basis for leukemia immunotherapy in patients with AML. Highlights: Th1 frequency and IFN-γ level were down-regulated in bone marrow of AML patients. NLRP3-activated BMDCs promoted CD4 + T cells differentiated into Th1 cells via secreting IL-1β. Elevated Th1 cells promoted apoptosis and inhibited proliferation of leukemia cells through secreting IFN-γ .